Exploring Lebanon's Growth Prospects - Berthélemy, Jean-Claude; Dessus, Sébastien; Nahas, Charbel (World Bank, Washington, DC, 2012)
This paper attempts to identify Lebanon's greatest constraints to economic growth, following a growth diagnosis approach. It concludes that fiscal imbalances and barriers to entry are most binding on long-term growth. Macroeconomic imbalances and related perceived risks affect the nature of investment decisions in Lebanon, in favor of liquid instruments rather than longer-term productive investments. Further, many barriers to entry discourage agents from investing in a number of markets: legal impediments to competition, corruption, and a set of fiscal incentives favoring the allocation of resources to non-tradable sectors, where potential demand and investment opportunities are scarcer. In turn, using a steady-state computable general equilibrium model, the paper assesses the long-term growth impact of a selected set of policy reforms envisaged to lift such constraints. Results suggest that 1 to 2 percentage points of additional GDP growth per year could be gained through public expenditure reform, greater domestic competition, and tax harmonization.